2018
DOI: 10.1111/chso.12306
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Education Centre Director Perceptions of Challenging Behaviour: Promising Practices and Implications for Professional Development

Abstract: Given their key role in overall programme quality, it is critical to examine how early childhood programme centre directors in the United States perceive challenging behaviour. Participants completed a survey asking which behaviours they perceive to be most problematic, the number of children dismissed or expelled from the programme during the last year, and the most commonly used strategies for addressing challenging behaviours. Results point to several promising practices and highlight the variability in acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…This also was a recurring theme mentioned by participants in the current study. While some researchers have studied professional development related to preparing future and current early childhood professionals on these topics, more work is needed in this area (Flower et al, 2017; Garrity, 2019; Hemmeter et al, 2008; Nenonene et al, 2019). Professional development and support from program leadership at community colleges and universities and within early childhood programs themselves must prioritize social emotional competence and place promotion and prevention at the forefront.…”
Section: Discussionmentioning
confidence: 99%
“…This also was a recurring theme mentioned by participants in the current study. While some researchers have studied professional development related to preparing future and current early childhood professionals on these topics, more work is needed in this area (Flower et al, 2017; Garrity, 2019; Hemmeter et al, 2008; Nenonene et al, 2019). Professional development and support from program leadership at community colleges and universities and within early childhood programs themselves must prioritize social emotional competence and place promotion and prevention at the forefront.…”
Section: Discussionmentioning
confidence: 99%
“…Teachers in the current study reported mixed feelings about the level of support they received from administrators, with some reporting that they felt very supported while others expressed frustration due to a lack of support. The important role of administrators related to children's challenging behavior is underscored in a study by Garrity et al (2019) who explored perceptions of challenging behavior, reasons for expulsion(s), and responses to challenging behavior by surveying administrators in NAEYC accredited early childhood programs. Findings were similar to those of teachers in the current study, with administrators reporting that they felt challenged by children's aggression and impulsivity.…”
Section: Anti-biased Early Childhood Educationmentioning
confidence: 99%
“…It is critical that educators recognize and address the impact of racism and ableism in classrooms, programs, and systems (Kulkarni et al, 2021). It also is essential for early childhood educators to be supported at the program and system level (Garrity et al, 2019). At the individual level, there are many resources available that focus on teaching practices.…”
Section: Implications For Practicementioning
confidence: 99%
“…On top of this, 14–30% of children entering early care and education programs are exhibiting problematic, challenging behaviors (Barbarin, 2007 ; Yoder & Williford, 2019 ), many of which are disruptive in the classroom. Because of this, classroom management and implementing positive behavioral supports are consistently identified as areas in which early childhood educators need additional training after they have begun working in a classroom setting (Garrity et al, 2019 ; Hemmeter et al, 2008 ; Snell et al, 2012 ). However, many early childhood educators report that they do not have access to high-quality PD opportunities that meet their and their classroom’s needs (Linder et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%